2018
DOI: 10.1002/bmb.21120
|View full text |Cite
|
Sign up to set email alerts
|

Preparing graduate student teaching assistants in the sciences: An intensive workshop focused on active learning

Abstract: In the past ten years, increasing evidence has demonstrated that scientific teaching and active learning improve student retention and learning gains in the sciences. Graduate teaching assistants (GTAs), who play an important role in undergraduate education at many universities, require training in these methods to encourage implementation, long-term adoption, and advocacy. Here, we describe the design and evaluation of a two-day training workshop for first-year GTAs in the life sciences. This workshop combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The last theme is "mobile" with the concepts "mobile", "education" and "networks" The emergence of the smartphones and mobile internet (e.g., 4G and 5G) "created a new social lifestyle" [188]. Thus, mobile applications are becoming increasingly important not only for m-banking, mgovernment and m-supply channels, but also for the "transformation of network teaching from the desktop computer to mobile teaching" [189].…”
Section: Automated Content Analysis Results For Articles From 5/1996 mentioning
confidence: 99%
“…The last theme is "mobile" with the concepts "mobile", "education" and "networks" The emergence of the smartphones and mobile internet (e.g., 4G and 5G) "created a new social lifestyle" [188]. Thus, mobile applications are becoming increasingly important not only for m-banking, mgovernment and m-supply channels, but also for the "transformation of network teaching from the desktop computer to mobile teaching" [189].…”
Section: Automated Content Analysis Results For Articles From 5/1996 mentioning
confidence: 99%
“…Few workshops have TAs teach their peers EBTP. For example, over the course of four years, Roden et al (16) implemented and assessed a 2-day, presemester ST workshop. Teaching assistants learned a ST practice in small groups, then, using the jigsaw method, shared their focal technique with their peers.…”
Section: Cherry On Topmentioning
confidence: 99%
“…However, there is a great deal of variability in the duration and content of these workshops, and often the focus is more on course logistics than on pedagogy (13). The Summer Institutes on Scientific Teaching (14,15)-with its emphasis on active learning, inclusive teaching, and assessment-has formed the basis for TAPD and workshops at several institutions (16,17). In some workshops, TAs actively model teaching practices to their peers (16); however, in most PD sessions, Building Excellence in Scientific Teaching: How Important Is the Evidence for Evidence-Based Teaching when Training STEM TAs?…”
Section: Introductionmentioning
confidence: 99%
“…Active learning is highly supported by the American Association for the Advancement Science [246], which publishes teaching materials that anyone can access at www.scienceintheclassroom.org. In the classroom, it is been shown that students and teachers (namely graduate students) who participate in active learning gain skills that drive analytical thinking [247], [248]. In museums, passive learning with guided tours results in lower levels of learning for children on the tour [249], whereas a well-designed activity supported by active learning pedagogy allows children to come to learning on their own [250].…”
Section: Active Learning In Science Education Pedagogy and Its Need In Higher Educationmentioning
confidence: 99%